Didaktische Perspektiven der Phraseologie in der Gegenwart Ansätze und Beiträge zur deutschsprachigen Phraseodidaktik in Europa - Mückel, Wenke (Formelhafte Sprache / Formulaic Language, 2022)
Phraseology has established itself as an independent academic discipline. Its applied subdiscipline, phraseodidactics, has developed somewhat delayed, but just as intensively. The articles in this volume analyze the current state of German phraseodidactics using examples and by providing a cross-section of phraseodidactic schools of thought, discourses, theoretical modellings, and methodological approaches.